Long-term changes in the geomagnetic field from observational data at magnetic observatories of Ukraine - Yu.P. Sumaruk (Геофизический журнал, 2011)
According to magnetometric data of the Ukrainian observatories "Kiev", "Lvov", "Odesa" the long-term changes of the component and module of geomagnetic field for the whole period of their observations have been analyzed depending on position of the observatories and solar and geomagnetic activities.